2020
DOI: 10.1051/e3sconf/202019706007
|View full text |Cite
|
Sign up to set email alerts
|

An appraisal of the application of open-cell foams in automotive SCR systems

Abstract: This work aims to investigate the possibility to apply open-cell foams as catalytic substrates in SCR systems for Diesel engines, as a replacement of traditional honeycombs. In the literature, many studies compare the performance of foams and honeycombs as catalytic substrates, showing, in general, a better mass transfer behavior in foams, compensated on the other hand by a higher pressure drop. In this work, we consider the low-pressure injection of Ad-Blue and we evaluate the performance of the open-cell foa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Such an application was tested on a chassis dynamometer and the experimental results showed that comparable pollutants' conversion efficiencies, with respect to traditional honeycombs, could be obtained with a lower amount of catalyst loading. Vespertini et al [7] conducted a preliminary numerical investigation on the application of a cubic POCS as an innovative mixing device for selective catalytic reduction (SCR) systems. Papetti et al [8] performed a comprehensive characterization of POCS structures as automotive catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Such an application was tested on a chassis dynamometer and the experimental results showed that comparable pollutants' conversion efficiencies, with respect to traditional honeycombs, could be obtained with a lower amount of catalyst loading. Vespertini et al [7] conducted a preliminary numerical investigation on the application of a cubic POCS as an innovative mixing device for selective catalytic reduction (SCR) systems. Papetti et al [8] performed a comprehensive characterization of POCS structures as automotive catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The startup phase of the engine represents a critical phase for the operation of the SCR system, as the temperatures of the components are well below the deposition temperature, and the fraction of UWS converted into ammonia is low, due to a reduced evaporation rate of the spray. To improve the performance of the system in these conditions, electrically heated catalyst (EHC) structures can be used in the role of both a pre-catalyst and a mixer: the possibility of adopting it as a mixer in an SCR after-treatment system has already been investigated in [4]. In particular, in this paper, a preliminary analysis is performed by considering a simplified structure representing a single row of struts of an EHC, and showing how different heating strategies can improve the conversion of UWS into ammonia in the cold start.…”
Section: Introductionmentioning
confidence: 99%